Direct medical costs of using enzalutamide or abiraterone in chemotherapy-naïve patients with metastatic castration resistant prostate cancer - N. A. Avxentyev; A. S. Makarov; M. Yu. Frolov (Фармакоэкономика)
Introduction. A number of drugs, which improve overall survival and quality of patients’ life, became available for treatment of metastatic castration-resistant prostate cancer (mCRPC). enzalutamide and abiraterone are the only two hormonal drugs increasing survival and approved for the treatment of mCRPC patients in Russia. The aim of the current study was to develop a pharmacoeconomic tool that calculates direct medical costs (price of the drugs) of using enzalutamide or abiraterone for treatment of chemotherapy-naïve patients with mCRPC from the Russian regional healthcare systems perspective. Materials and methods. The calculator is based on a published pharmacoeconomic model of using enzalutamide or abiraterone for the 1st line treatment of mCRPC. Current regional medication prices, which explain the biggest share of direct medical treatment costs, are automatically accounted for 84 Russian regions (except nenetsky AO). The calculator also provides estimates of number of chemotherapy-naïve patients, who are eligible for enzalutamide or abiraterone treatment in each region. Results. Costs of using enzalutamide or abiraterone are almost equal on the federal level, but the differences in the costs between these two medications are higher than 10% in 15 Russian regions. Conclusions. Possible differences in costs of using enzalutamide or abiraterone should be accounted during planning of state procurements on the regional level.